Genetic diversity of the tall-stilt mangrove (Rhizophora apiculata Blume) in Southern Central Coast of Vietnam using SSR markers - Hong Nguyen, Nhung; Nguyen, Trong Dinh; Thi Tran, Giang Huong; Quoc Nguyen, Huy; Pham, Ngoc Bich; Hoang Chu, Ha; Vu Dinh, Duy; Do, Phat Tien (Academia Journal of Biology, 2025)
Rhizophora apiculata is one of the important mangrove species for coastal communities and the global ecosystem. However, it has been threatening due to land clearing and over-exploitation, particularly in the Southern Central Coast of Vietnam. The SSR-PCR analysis indicated low levels of genetic diversity in R. apiculata populations distributed in the Southern Central regions of Vietnam. The observed number of alleles (NA) was 1.933 indicating a low polymorphism for surveyed overall loci in tested populations. The observed heterozygosity (HO) was also less than 0.5 indicating low heterozygosity at the species level. The interpopulation genetic diversity for each locus ranged from 0.000 to 0.188 demonstrating a moderate genetic differentiation among tested populations. Results of AMOVA analysis indicated that genetic variation almost occurred within the population (88%). Moreover, genetic distances of R. apiculata populations were low (drifted less than 0.05) indicating the gene pool exchange. At the overall population level, two different groups were observed and confirmed from UPGMA analysis and genetic distance matrix data. To gain a comprehensive understanding of the genetic diversity of R. apiculata in the Southern Central Coast of Vietnam, it would be necessary to utilize more molecular markers and investigate the matter further in other coastline regions. This would provide recommendations for mangrove tree breeding and restoring the mangrove forests in Vietnam as well as support for coping with the change of global climate.